PLANNING TO OPTIMIZE CONDENSATION WATER FOR CLEAN WATER NEEDS AT THE AIRPORT - Saputra, Akbar Nopriansyah; Burhanuddin, Fachrurrazi (Journal of Airport Engineering Technology (JAET), 2025)
Condensation water from air conditioning can be used as an alternative water source because it still contains few minerals, has a low temperature, and maintains quality. However, until now, this condensation water has not been utilized for airport operational activities. This water could be used to water plants that have previously used up 5,000 liters of clean water. This research aims to design a water tank or reservoir for condensation water so that it is easy to distribute. The Research and Development method (R&D) using the 4D Model starts with definition (define), planning (design), development (develop), and dissemination (disseminate) limited to the design stage. The results of this study are presented in the form of a 3-dimensional design plan for a 50,000-liter condensation water storage system, equipped with a piping system, control tank, and pump to distribute the water. This study has received design validation from material experts and supervisors of the airport's mechanical unit. The validation results indicate a functional aspect assessment value of 77.5% (Good) and a quality aspect of 82% (Good), suggesting that further tank maintenance systems should be considered. Based on this assessment, the design of the condensation water optimization plan is deemed feasible for implementation.